Preparation, structure and useful properties of poly(e-caprolactone)/layered silicates nanocomposites - Pigłowski, J.; Kiersnowski, A.; Dołęga, J. (Polimery, 2022)
The article is a review of literature concerning the results of past investigations of nanocomposites consisted of poly(e-caprolactone) (PCL) matrix and montmorillonite (MMT) as a filler. The structure (Fig. 1), properties and possibilities of MMT modifications with various amphiphilic compounds were presented. As well the selected PCL properties, especially its biodegradability and compatibility with many other polymers were discussed. Two main methods of preparation of PCL/MMT composites were characterized namely melt blending and in-situ way via polymerization of e-caprolactone in the presence of organophilized MMT (Fig. 2). The selected mechanical properties of micro- and nanocomposites of PCL with different filler contents (Table 1, Fig. 3) as well as of composites with polymer matrix consisted of PCL blend with another polymers (PVC, PP, PE or SAN, Table 2) were discussed. Barrier properties and thermal stability of the composites discussed were also characterized.